PERBANDINGAN DAN TREND KINERJA KEUANGAN BPRS SELAMA LINKAGE PROGRAM DENGAN BANK SYARIAH PERIODE 2011 - 2016 (STUDI KASUS BPRS BAKTIMAKMUR INDAH, BPRS BHAKTI SUMEKAR, DAN BPRS PNM MENTARI) - Muchamad Ichwan Subagiyo; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
The research aims to discover whether there are any differences in financial performance between Sharia Rural Bank (SRB) which take part in the linkage program and this study was to determine the trend of financial performance in period 2011-2016. The method used in this research is quantitative. The sample were SRB Baktimakmur Indah, SRB Bhakti Sumekar and SRB PNM Mentari and then carried out the analysis different test using ANOVA and Kruskal Wallis test. The variables used in financial performance assessment are ROA, ROE, BOPO, NPF, FDR, and CAR. The data used for this study are secondary data gathered from financial report. Trend analysis of this research showed that SRB Bhakti Sumekar have a good growth in ratio of ROA, ROE, BOPO, NPF and FDR, but SRB Baktimakmur have the most growth in ratio of CAR. Differences in financial performance viewed from ROE, BOPO, NPF, FDR, CAR. But, ROA do not any differences. REFERENCESAnshori, Muslich dan Iswati. 2009. Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Press.Bank Indonesia. 2001. Lampiran Surat Edaran BI No. 3/30/DPNP Perihal Sistem Penilaian Tingkat Kesehatan Bank Umum Berdasarkan Prinsip Syariah. Jakarta: Bank Indonesia_____________. 2004. Arsitektur Perbankan Indonesia (API)  _____________. 2004. Generic Model Linkage program  _____________. 2007. Lampiran Surat Edaran No. 9/24/DPbS Perihal Sistem Penilaian Tingkat Kesehatan Bank Umum Berdasarkan Prinsip Syariah. Jakarta: Bank Indonesia_____________. 2016. Publikasi Laporan Keuangan BPRS. (online), (www.bi.go.id, diakses 23 Oktober 2016)Dendawijaya, Lukman. 2005. Manajemen Perbankan, Edisi Kedua, Cetakan Kedua. Bogor: Ghalia Indonesia.Ismail. 2011. Perbankan Syariah. Jakarta: Kencana Media Group  Ismail. 2014. Sejarah Perkembangan BPR-Syariah di Indonesia. (online), (http://ismail125cc.blogspot.co.id diakses 16 September 2016)Kasmir. 2013. Analisis Laporan Keuangan. Jakarta: PT Raja Grafindo Persada.Mahmudi. 2010. Analisa Laporan Keuangan Pemerintah Daerah. Yogyakarta: STIM YKPNRepublik Indonesia. 2008. Undang-Undang Nomor 21 Tahun 2008 Tentang Perbankan Syariah. Jakarta: Republik IndonesiaRepublik Indonesia. 2009. Peraturan Nomor : 03/Per/M.KUKM/III/2009 Menteri Negara Koperasi Dan Usaha Kecil Menengah Nomor 03/PER/M.KUKM/III/2009 Tentang Linkage program. Jakarta: Republik IndonesiaRivai, Veithzal dan Arifin. 2008. Islamic Banking Sebuah Teori, Konsep, dan Aplikasi. Jakarta: Bumi Aksara.Santoso, Singgih. 2013. Menguasai SPSS di Era Informasi. Jakarta: Elex Media Komputindo.